Superconvergence Analysis for the Stable Conforming Rectangular Mixed Finite Elements for the Linear Elasticity Problem (Journal of Computational Mathematics, 2018)
In this paper, we consider the linear elasticity problem based on the Hellinger-Reissner variational principle. An $\mathcal{O}(h^2)$ order superclose property for the stress and displacement and a global superconvergence result of the displacement are established by employing a Clément interpolation, an integral identity and appropriate postprocessing techniques.